Principles of Accounting. - Wegman, David E.; Hendrickson, Harvey S. (The Accounting Review, 1987)
Reviews the book 'Principles of Accounting,' 2nd ed., by John G. Helmkamp, Leroy F. Imdieke and Ralph E. Smith.